Effectiveness of life skills training based on self-care on mental health and quality of life of married Afghan women in Iran - Fatemeh Abbasi Shovaz; Hassan Zareei Mahmoodabadi; Maryam Salehzadeh (BMC, 2022)
Abstract Background One of the major issues that immigrants, especially Afghan women face, is their self-care disability. This will cause problems in their mental health and quality of life. The aim of this study was to evaluate the effectiveness of life skills training based on self-care on mental health and quality of life of married Afghan women living in Taft. Methods This quasi-experimental study was conducted using a pretest posttest design with control group. Statistical population was all married Afghan women living in Taft (Yazd province) of whom 60 women were selected using purposive sampling and were randomly allocated to two groups of 30 as experimental and control groups. The experimental group received 8 sessions of life skills training based on self-care. General Health Questionnaire (GHQ) and Quality of Life of the World Health Organization Questionnaire (WHOQ-BREF) were used to collect data. Multivariate analysis of covariance (MANCOVA) was used to analyze the data. Results Results showed that following the intervention, the mean scores of quality of life (p < 0.0001) and mental health (p < 0.019) in the experimental group increased in the posttest compared to the pretest and the effect of intervention was significant. Conclusion Results suggested that providing a training opportunity for Afghan women to learn life skills based on self-care, enables them to realize their strengths and weaknesses and improve their quality of life and mental health.